Gagasan Pengaturan Bank Tanah untuk Mewujudkan Pengelolaan Aset Tanah Negara yang Berkeadilan - Al Zahra, Fatimah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The complexity of the land problem is an unresolved issue. The fact that the amount of land is fixed, while the need for physical development is increasing as the increase in population leads to inevitable social conflict. One of the causes of social conflict is the conflict of interest between the government that needs land for the construction of various infrastructure and the people who want to retain the rights to the land it owns. Therefore, it is necessary to revise the land policy that leads to the integrated state land asset mechanism that can accommodate the needs of the government and the right of the people as the owner of the land rights simultaneously, so that social justice for all Indonesian people can be realized. Implementation of the land bank concept as a means of integrated state land assetsmanagement can be a solution in overcoming the land crisis for development.